GEOLOGY OF KAMPUNG BAHARU, SIMPANG AMPAT GUNONG SEMANGGOL WITH EMPHASIS ON FEEDER CHANNEL MORPHOLOGY - BIN SHUHAIMI, MUHAMMAD YAZID (Universiti Teknologi PETRONAS, 2014)
This project outlines the study on general geology of Kampung Baharu, Simpang Ampat Gunong Semanggol and describe its geomorphology. The study area is part of the southern Semanggol Formation. Semanggol Formation are deposited in the fore deep basin where it is formed over the leading edge of Sibumasu and the accreationary complex (Metcalfe, 2013). In order to study the geology and geomorphology of study area, the main methodologies done are literature studies, geological fieldworks, generate maps, analyses rock samples and bedding geometries and develop the study area models. The results show that the area have 4 different lithology which are conglomerates, sandstone, siltstone and soft clay which are been grouped into a conglomerate unit. The unit is in repeated cycles which indicate episodes of uplifting and depositions. All of the rocks composed of same minerals which are quartz and feldspar. The study area is interpreted as a feeder canyon zone in the Semanggol turbidite system. The canyon dimension is estimated to be 300m wide and 150m deep. The source of conglomerate units are probably from Bintang granite which 40km Northeast from the study area and deposited during Early to Middle Triassic. Nevertheless, the study area is an interesting area to understand the turbidite system and other parts of Semanggol Formation should be covered for further research.